Fine root biomass of European beech trees in different soil layers show different responses to season, climate, and soil nutrients - Likulunga, Likulunga Emmanuel; Clausing, Simon; Krüger, Jaane; Lang, Friederike; Polle, Andrea (Frontiers in Forests and Global Change, 2022)
Fine roots are crucial for water and nutrient acquisition in plants; yet it is unknown how nutrient inputs and soil fertility in forests influence fine root biomass seasonal trajectories.Here , we hypothesized that standing fine root biomass increases with addition of a limited resource and shows different seasonal patterns depending on nutrient availability and phenology. We further hypothesized that the influence of climate is greater in the organic layer, causing larger responses of root biomass to climate in the organic layer and stronger responses to nutrient changes in mineral soil. We conducted our study in three European beech (Fagus sylvatica) forests representing a soil fertility gradient with high, medium, and low phosphorus (P) contents. A fully factorial fertilization regime with N and P was applied at each forest site. To test our hypotheses, we conducted soil coring in spring and fall for 2.5 years. Soil cores were fractionated into organic layer (Oe+Oa layer) and mineral soil (A horizon) and used to determine fine root biomass, soil pH and moisture, total concentrations of soil and root nutrients (basic cations, micronutrients, S, P, N, C), soluble concentrations of soil and root P. Fine root biomass in the mineral soil at the forest site with the lowest soil P content increased in response to P addition. Pheno-seasonal changes caused increases in soil P and N in spring and opposing cycling of biomass and fine root labile P contents at the P-medium and P-high sites. Contrary to our expectation, we observed stronger climatic effects on fine root biomass in the mineral soil, whereas soil moisture was more important in explaining fine root biomass variation in the organic layer. Our results show that seasonal patterns of fine root biomass are dependent on the stratification of environmental factors with soil depth and imply negative consequences for fine root biomass in the organic soil layer due to acute soil water content fluctuations and climate change effects in the mineral horizon due to long-term precipitation changes.